Basic education for Indigenous peoples in Indonesia: Limiting children's cultural alienation and loss of identity - Uus Faizal Firdaussy; Ningsih, Sri; Enkin Asrawijaya (Issues in educational research, 2024)
Our study explores challenges and opportunities associated with managing basic education in Indigenous communities in Indonesia, using a qualitative descriptive approach with a critical paradigm as an analysis tool. The findings reveal two types of education patterns for Indigenous peoples, i.e., education in the community, which is carried out within families or the community without formal schooling, and formal education organised by the government. Indigenous children confront significant challenges in accessing quality education due to economic factors, minimal facilities and infrastructure, and a shortage of teachers. In addition, at times the national education systems do not consider the special needs and characteristics of Indigenous peoples. We propose an inclusive education curriculum for Indigenous children that focuses on providing quality education and preserving cultural heritage.